Alberto Montt in daily doses. - Montt, Alberto (Santiago, Chile : [publisher not identified], 2010)
Alberto Montt in Daily Doses is a webcomic created by Alberto Montt.
Preserved in: Global webcomics web archive (Ivy Plus Libraries).
Identification of the resource based on contents viewed on July 18, 2018; title from home page.
Keywords: Webcomics; Funny animal comics; Comics (Graphic works); Comics (Graphic works); Funny animal comics